PENGEMBANGAN MEDIA PEMBELAJARAN LUDO TERINTEGRASI PROFIL PELAJAR PANCASILA PADA MATERI JENIS UANG KELAS IV SDN JATIREJO KALIGESING PURWOREJO - Dwi Nugraini; Arum Ratnaningsih; Muflikhul Khaq (STKIP Subang, 2024)
The learning process implemented is one-way, causing learning to become boring and uninteresting. Therefore, this research aims to: 1) Produce a product in the form of Integrated Ludo Learning Media Development for Pancasila Student Profiles on Class IV Money Types at SDN Jatirejo Kaligesing Purworejo which is in accordance with research and development development procedures. 2) What is the feasibility of developing Integrated Ludo Learning Media for Pancasila Student Profiles in Class IV Money Types at SDN Jatirejo Kaligesing Purworejo. The type of research used in research is research and development. The research model uses Borg and Gall which consists of 10 development stages. The research subjects were class IV students at SDN Jatirejo for the 2023/2024 academic year with a total of 17 students. The data collection techniques used were observation, interviews and questionnaires. The data collection instruments used consisted of observation sheets, interviews, media expert validation questionnaires, materials, teachers and student responses. The data analysis techniques used are feasibility analysis and practicality analysis. The results of this ludo media development research are: 1) This research produces a product in the form of Integrated Ludo Learning Media for Pancasila Student Profiles on Class VI Money Types at SDN Jatirejo Kaligesing Purworejo. 2) The product feasibility results obtained an average score of 90% which was in the